Loss or silencing of the PHD1 prolyl hydroxylase protects livers of mice against ischemia/reperfusion injury - Schneider, Martin; Van Geyte, Katie; Fraisl, Peter; Kiss, Judit; Aragonés, Julián; Mazzone, Massimiliano; Mairbäurl, Heimo; De Bock, Katrien; Jeoung, Nam Ho; Mollenhauer, Martin; Georgiadou, Maria; Bishop, Tammie; et al. (Gastroenterology, 2010)
Liver ischemia/reperfusion (I/R) injury is a frequent cause of organ dysfunction. Loss of the oxygen sensor prolyl hydroxylase domain enzyme 1 (PHD1) causes tolerance of skeletal muscle to hypoxia. We assessed whether loss or short-term silencing of PHD1 could likewise induce hypoxia tolerance in hepatocytes and protect them against hepatic I/R damage.